Blending a relationship-based approach to a community-based approach: A case study in the Tamang community of Rasuwa, Nepal - Tatsumi, Kazuko; Tamang, Phurpa (Nepal Sociological Journal, 2025)
The rapid diffusion of modernization, globalization, technology, and modern education has affected rural people and their conventional way of life. Rural areas have become an aging rural society experiencing the negative effects caused by younger generations migrating to urban areas. In the SASON conference 2013, the authors pointed out that rural people have the potential to create a model for the harmonization of modern development with community-based cultural tourism. Because of the COVID Pandemic, the dependence on tourism development increases vulnerability. Taking reference from Özşen’s (2020) framework of a ‘relation-based mobilized community’, this study attempts to find a new perspective to shift from a ‘community-based approach’ to a ‘relationship-based approach’. In general, when considering rural development, the community-based approach focuses on permanent populations within geographical and administrative borders. By analyzing the actual situation with a ‘relationship-based approach’, the findings of this study indicate that rural families and their community are supported by external family members, kinship, and social relations. Their remittances have contributed to rural families. Mobile phones and social networking services play significant roles in allowing them to communicate with each other. The young-middle generations who come and go in their communities bring not only money but also new skills and a new, more worldly outlook. The economic issues in rural areas have been found as job creation and income generation. Accordingly, people are gradually losing their pride and sense of identity in their community. As these characteristics have caused many social problems, multifunctional rural development is necessary. The analysis is based on the review of literature, primary/secondary data, and fieldwork that has been carried out since 2000 in Rasuwa. In the spring of 2023, we conducted a questionnaire survey, interviews with key people, and observation.